Moon mission! - Osborne, Mary Pope (Red Fox London, 2008)
Jack and Annie are on the moon. The tree house whisks them into the future - to an exciting outer-space hotel. But they've only got two hours before they run out of air. Will the moon man and his map help them get back safely?